2022
DOI: 10.1186/s40462-022-00308-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternative migratory strategies related to life history differences in the Walleye (Sander vitreus)

Abstract: Background While Pace of Life Syndrome predicts behavioural differences between individuals with differential growth and survival, testing these predictions in nature is challenging due to difficulties with measuring individual behaviour in the field. However, recent advances in acoustic telemetry technology have facilitated measurements of individual behaviour at scales not previously possible in aquatic ecosystems. Methods Using a Walleye (Sander… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
2
1
Order By: Relevance
“…Superior walleye (McKee et al, 2022). Their study found migratory walleye were slightly larger than residents and predominantly female; however, size was not a significant predictor of variability in displacement distances in our study and sex was not obtained for our tagged fish.…”
Section: Discussioncontrasting
confidence: 76%
“…Superior walleye (McKee et al, 2022). Their study found migratory walleye were slightly larger than residents and predominantly female; however, size was not a significant predictor of variability in displacement distances in our study and sex was not obtained for our tagged fish.…”
Section: Discussioncontrasting
confidence: 76%
“…Further, Hayden et al (2014) tagged adult Walleye that were included in this study and reported that 95% of the fish were detected moving from the river release site into Saginaw Bay of Lake Huron within 21 days, supporting low postrelease mortality or tag shedding and suggesting that recently tagged fish are capable of rapid movement. These results were expected due to the number of years spent developing and evaluating surgical procedures for implanting transmitters (Cooke et al 2011;Schoonyan et al 2017) and the widespread use of these transmitters in the Great Lakes (Hayden et al 2014;Brooks et al 2019;Faust et al 2019;McKee et al 2022). Additionally, premature failure of transmitters occurred at an overall rate (2%) that seems unlikely to compromise inferences that are made from many telemetry-based studies that use similar transmitters.…”
Section: Discussionmentioning
confidence: 96%
“…2019; McKee et al. 2022). Additionally, premature failure of transmitters occurred at an overall rate (2%) that seems unlikely to compromise inferences that are made from many telemetry‐based studies that use similar transmitters.…”
Section: Discussionmentioning
confidence: 99%